2003
DOI: 10.4049/jimmunol.171.2.821
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cooperation of Simian Virus 40 Promoter Factor 1 and CCAAT/Enhancer-Binding Protein β and δ in Lipopolysaccharide-Induced Gene Activation of IL-10 in Mouse Macrophages

Abstract: Previous studies have revealed that LPS can activate transcription of the IL-10 gene promoter through an SV40 promoter factor 1 (Sp1) binding site in mouse macrophage RAW264.7. In this study, we determined that, in addition to Sp1, C/EBPβ and δ were also involved in LPS-induced gene expression of IL-10. By transient transfection with 5′-deletion mutants of the IL-10 promoter, we found that there were two LPS-responsive elements in the promoter of the mouse IL-10 gene. Analysis of these two regions by gel shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 47 publications
7
78
1
Order By: Relevance
“…The protein interaction between Sp1 and C/EBPb or between Sp1 and C/EBPd upon the LPS treatment was also confirmed by coimmunoprecipation [45]. In the present study, we studied further the interaction between C/EBPd and Sp1, mapped the proteinprotein interaction domains, and found that the major interaction domains of C/EBPd and Sp1 were located in their C-termini.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The protein interaction between Sp1 and C/EBPb or between Sp1 and C/EBPd upon the LPS treatment was also confirmed by coimmunoprecipation [45]. In the present study, we studied further the interaction between C/EBPd and Sp1, mapped the proteinprotein interaction domains, and found that the major interaction domains of C/EBPd and Sp1 were located in their C-termini.…”
mentioning
confidence: 85%
“…Cells were transfected with 0.2 lg of luciferase reporter plasmid, 0.8 lg of pPac-Sp1, and 0.4 lg of pPac-C/EBPd for 48 h, and then luciferase activity assay was performed as previous report [45]. Variable amounts of expression plasmids were compensated with the empty vector pPac.…”
Section: Transfection Of Sl2 Cells By Calcium Phosphate Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies, LPS has been shown to activate IL-10 gene expression through Sp1. 34,35 Brightbill et al 35 showed that transfection of a murine macrophage cell line with the IL-10 promoter construct resulted in an eightfold increase on LPS stimulation. These results are in line with the results presented in the current study.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lmentioning
confidence: 99%
“…Candidate regulators can be identified by analysis of promoters of M2-specific genes in macrophages, and among these, the Il10 and Arg-1 promoters are regulated by C/EBP␤ (9,10). C/EBP␤ is a member of the C/EBP family of basic region-leucine zipper (bZIP) proteins and is known to be important for the antibacterial activity of macrophages (11).…”
mentioning
confidence: 99%